2018
DOI: 10.22159/ajpcr.2018.v11i1.22533
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Interrelationship Between Electrolytes, Anemia, and Glycosylated Hemoglobin (Hba1c) Levels in Type 2 Diabetics

Abstract: Objective: The aim of this study is to analyze the interrelationship and pattern of electrolyte imbalance and compare the correlation between serum electrolytes, glycosylated hemoglobin (HbA1C), and hemoglobin (Hb) levels between Type 2 diabetic patients and non-diabetic subjects. Methods:This study was conducted in 300 subjects (150 diabetics and 150 non-diabetics) and further categorized as anemic and non-anemic within each group. Blood samples were analyzed for HbA1C, hemoglobin, and serum electrolyte level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 16 publications
(20 reference statements)
0
9
0
Order By: Relevance
“…Hyperkalaemia is common in DM. 7 , 21 , 22 Conversely, studies conducted in Nigeria and Saudi Arabia found a predominant hypokalaemia and no significant association between serum potassium levels and glycaemic control, respectively. 23 , 24 Similarly, our study found no significant association between HbA1c and serum potassium levels.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Hyperkalaemia is common in DM. 7 , 21 , 22 Conversely, studies conducted in Nigeria and Saudi Arabia found a predominant hypokalaemia and no significant association between serum potassium levels and glycaemic control, respectively. 23 , 24 Similarly, our study found no significant association between HbA1c and serum potassium levels.…”
Section: Discussionmentioning
confidence: 95%
“…serum sodium levels were significantly lower in patients with DM compared with non-DM controls (127.92 [0.45] mmol/L vs. 135.82 [0.34] mmol/L; p = 0.0001) and that HbA1c was significantly inversely correlated with serum sodium levels ( r = 0.640; p = 0.0001). 7 However, no regression analysis was performed in the study conducted in India. 7 Other causes of hyponatraemia in DM include side effects of drugs such as diuretics, diabetic nephropathy and the syndrome of inappropriate antidiuretic hormone secretion (SIADH).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, the prevalence of morphologically different types of anemia in Gurugram, Haryana is lower than other areas. The others various scientific studies have been observed that anemia is conditions which are associated with many health conditions like diabetes, cardiovascular, retinopathy, renal, and others 16 .…”
Section: Discussionmentioning
confidence: 98%